The Public Dimension of Renato Constantino’s ‘Historically-Informed Social Criticism’: Facets and Critiques of His Intellectual Legacy, 1945-1978 - Guiang, Francisco Jayme Paolo A. (Philippine Social Sciences Review; PSSR Vol. 72 No. 1 2020, Ed. Jorge V. Tigno, 2021)
This article examines Renato Constantino’s seminal works using what the American historian Christopher Lasch calls a “historically-informed social criticism” as a guide to underscore the public dimension of the former’s intellectual legacy. As an initial step, it reviews the appraisals on Constantino to identify what has been written about the scholar and what remains unexplored. It then probes into the manner by which the scholar had articulated his nationalist thinking by revisiting his public career as a journalist and a public intellectual. Lastly, this article interrogates the substantial part of Constantino’s intellectual legacy by looking at the contingent roles of his social criticisms and historical elucidations which comprise the core components of his corpus of writings.